PERANAN LABORATORIUM DALAM PENEGAKKAN DIAGNOSIS DI PUSKESMAS MASBAGIK TAHUN 2022 - Dwi Fratika Safitri; Fatriyawan, Abdul Aziz (Nusadaya Journal of Multidiciplinary Studies, 2022)
The importance of laboratory testing is needed in terms of making a diagnosis. Medical support service laboratories are needed by doctors in diagnosing, monitoring and prognosticating diseases so as to minimize unnecessary treatment or therapy. This study aims to determine the role of the laboratory in establishing a diagnosis at the Masbagik Health Center in 2022. This research method uses descriptive quantitative methods. The population in this study were 97 respondents with accidental sampling technique. The sampling method is by distributing questionnaires to outpatients at Masbagik Health Center.The results of the study were based on the Univariate Analysis Test with a total of 97 people (100.0%) respondents who were used as research samples. There are 56 respondents (57.7%) who underwent laboratory testing, while 41 respondents who did not undergo laboratory testing (42.3%). So from these results it can be seen that Laboratory Testing plays a significant role in establishing a diagnosis, namely > 50% of all respondents.